A Study of Learning Achievement on the Direct Current and the 21st Century Life and Career Skills of Grade 11 Students Using Project-Based Learning - น้อยเจริญ เจนจิรา; เนาวนนท์ อดิศร (Ratchaphruek Journal, 2019)
The purposes of this research were to 1) compare pre-test and post-test of learning achievement on the direct current, 2) compare learning achievement on the direct current of students after using project method with 60% criteria,3) study the quality of product after learning project method, and 4) compare pre-test and post-test of life and career skills. The sample of this research was 40 students of grade 11th students in the second semester of the 2017 academic year at Pak Chong 2 School, Nong Sa Rai Sub-district, Pak Chong District, Nakhon Ratchasima Province. The research instruments were lesson plan, learning achievement test, students’ work evaluation form of life and career skills in the 21st century test. After that, data were analyzed by mean, percentage, standard deviation and dependent t-test. The result of research were showed that: 1) Students’ self-study, develop their knowledge and made their learning achievement in post-test significantly to be higher than pre-test scores., 2) Students had their learning achievement in post-test to be higher than 60% criterion, 3) From the project-based learning management, students had create concrete works. All of the quality of the works were at the excellent level, and 4) Students had life and career skills in the 21st century. The result of research, students to become enthusiastic in their study and what they need. Working as a group and contributes to the skills of living together, adjusting to each other. Problem solving made students develop knowledge and life skills. Besides, from result of empirical work, students can use knowledge to apply in their career after.